Pengaruh Motivasi Kerja terhadap Produktifitas Kerja Karyawan PT. Persada Lampung Raya - Soewito; Suhartina; Mohammad Ridwan Setiawan (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2022)
One company that prioritizes the productivity of its employees, namely PT. Persada Lampung Raya which is a company engaged in the automotive sector of four-wheeled vehicles with the Suzuki brand in Lampung Province. The purpose of this study was conducted at PT. Persada Lampung Raya is to find out whether work motivation has an influence on employee productivity at PT. Persada Lampung Raya. In this study the authors use a quantitative research approach with a population of 105 employees of PT. Persada Lampung Raya while the sample used 46 respondents. The analytical tool used is assisted by the computerized program SPSS version 25. Based on the results of the research work motivation has an influence on the work productivity of employees of PT. Persada Lampung Raya. With the tcount value of Work Motivation of 21,803 with a Sig value of 0.000. This shows that the hypothesis Ha is accepted and Ho is rejected. So that it can be interpreted that the work motivation variable (X) has an influence on (Y) the work productivity of employees of PT. Persada Lampung Raya. Keywords : work motivation, work productivity